Sex Differences in Adrenal Bmal1 Deletion–Induced Augmentation of Glucocorticoid Responses to Stress and ACTH in Mice - Engeland, William C (Endocrinology, 2019)
The circadian glucocorticoid (GC) rhythm is dependent on a molecular clock in the suprachiasmatic nucleus (SCN) and an adrenal clock that is synchronized by the SCN. To determine whether the adrenal clock modulates GC responses to stress, experiments used female and male Cyp11A1(Cre/+)::Bmal1(Fl/Fl) knockout [side-chain cleavage (SCC)–KO] mice, in which the core clock gene, Bmal1, is deleted in all steroidogenic tissues, including the adrenal cortex. Following restraint stress, female and male SCC-KO mice demonstrate augmented plasma corticosterone but not plasma ACTH. In contrast, following submaximal scruff stress, plasma corticosterone was elevated only in female SCC-KO mice. Adrenal sensitivity to ACTH was measured in vitro using acutely dispersed adrenocortical cells. Maximal corticosterone responses to ACTH were elevated in cells from female KO mice without affecting the EC(50) response. Neither the maximum nor the EC(50) response to ACTH was affected in male cells, indicating that female SCC-KO mice show a stronger adrenal phenotype. Parallel experiments were conducted using female Cyp11B2 (Aldosterone Synthase)(Cre/+)::Bmal1(Fl/Fl) mice and adrenal cortex–specific Bmal1-null (Ad-KO) mice. Plasma corticosterone was increased in Ad-KO mice following restraint or scruff stress, and in vitro responses to ACTH were elevated in adrenal cells from Ad-KO mice, replicating data from female SCC-KO mice. Gene analysis showed increased expression of adrenal genes in female SCC-KO mice involved in cell cycle control, cell adhesion–extracellular matrix interaction, and ligand receptor activity that could promote steroid production. These observations underscore a role for adrenal Bmal1 as an attenuator of steroid secretion that is most prominent in female mice.